EKOLITERASI SANTRI GENERASI Z: KESADARAN DAN PERILAKU LINGKUNGAN BERBASIS PESANTREN - MR, Maghfur (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2025)
Environmental damage in Indonesia remains a serious problem, despite an increase in the National Environmental Quality Index (IKLH). The involvement of religious educational institutions, particularly Islamic boarding schools (pesantren), is a potential strategy in building ecological awareness among young generations, especially Generation Z students at pesantren. As a generation that is digitally savvy while also guardians of pesantren traditions, Generation Z students have the ability to form pesantren-based environmental change movements. This study aims to describe the eco-literacy habitus model of Generation Z pesantren students through a library research approach using a descriptive qualitative method. The study focuses on the integration of Islamic values, pesantren education, and the characteristics of Generation Z in shaping eco-literate habits. Referring to recent academic literature, it was found that the process of ecoliteracy habituation in the context of pesantren involves four main dimensions: cognitive (head), affective (heart), psychomotor (hands), and spiritual (spirit). Generation Z santri are able to internalize ecological values based on Islam due to their digital skills and social adaptability. This study recommends strengthening the pesantren ecopedagogy curriculum in synergy with digital literacy and environmental fiqh.